IMPLEMENTASI KRIPTOGRAFI KOMBINASI ALGORITMA VIGENERE CIPHER DAN REVERSE CIPHER UNTUK KEAMANAN TEKS PADA APLIKASI CATATAN PRIBADI BERBASIS ANDROID - Siregar, Muhammad Faisal; Hasugian, Abdul Halim; Suhardi, Suhardi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: Cryptography (Cryptography) is the science and art of keeping messages safe. (Cryptography is the art and science of keeping messages secure) "Crypto" means "secret" and "graphy" means "writing". The perpetrators or practitioners of cryptography are called cryptographers. A cryptographic algorithm, called a cipher, is a mathematical equation used for the encryption and decryption processes. Usually the two mathematical equations (for encryption and description) have a fairly close mathematical relationship. In cryptography, text messages can be disguised with various methods so that the message can only be understood by certain people. These methods have their own techniques and solutions. Several methods of securing text messages are by using the Reverse Cipher and Vigenere Cipher algorithms. In today's modern era, the development of technology is increasing rapidly, especially in terms of communication. Due to the rapid development of technology, there are currently many cases related to the misuse of technology in criminal acts. One of the most frequent cases is the theft of personal information, up to confidential documents. Computers as a means of storing and sending important and confidential data, information and documents can often be easily accessed by irresponsible people. Several cases involving computer security are currently a job that requires such a large amount of handling and security costs. Keywords: Cryptography, Reverse Cipher, Vigenere Cipher, Description, Encryption Abstrak: Kriptografi (Cryptography) merupakan ilmu dan seni untuk menjaga pesan agar aman. (Cryptography is the art and science of keeping messages secure) “Crypto” berarti “secret” (rahasia) dan “graphy” berarti “writing” (tulisan). Para pelaku atau praktisi kriptografi disebut cryptographers. Sebuah algoritma kriptografik (cryptographic algorithm), disebut cipher, merupakan persamaan matematik yang digunakan untuk proses enkripsi dan deskripsi. Biasanya kedua persamaan matematik (untuk enkripsi dan deskripsi) tersebut memiliki hubungan matematis yang cukup erat. Pada kriptografi, pesan teks dapat disamarkan dengan berbagai macam metode agar pesan tersebut hanya bisa dimengerti oleh orang-orang tertentu. Metode-metode tersebut memiliki teknik dan cara penyelesaiannya tersendiri. Beberapa metode pengamanan pesan teks tersebut adalah dengan menggunakan algoritma Reverse Cipher dan Vigenere Cipher. Di era modern saat ini, perkembangan teknologi semakin pesat terutama dalam hal berkomunikasi. Karena pesatnya perkembangan teknologi, saat ini telah banyak kasus yang berkaitan dengan penyalahgunaan teknologi dalam tindakan kriminal. Salah satu yang paling sering terjadi adalah pencurian informasi pribadi, hingga dokumen-dokumen rahasia. Komputer sebagai sarana penyimpanan dan pengiriman data, informasi, dan dokumen yang penting dan rahasia sering dapat dengan mudah diakses oleh orang yang tidak bertanggungjawab. Beberapa kasus menyangkut keamanan komputer saat ini menjadi suatu pekerjaan yang membutuhkan biaya penanganan dan pengamanan yang sedemikian besar. Kata kunci: Kriptografi, Reverse Cipher, Vigenere Cipher, Deskripsi, Enkripsi